Pengaruh Inflasi dan Indeks Harga Konsumen Terhadap Laju Pertumbuhan PDRB di Kota Bandar Lampung Tahun 2012-2019 - Yulia Lestari; Resta Uke Yurinda; Misfi Laili Rohmi (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
Achieving human development requires GRDP because economic guarantees will increase income and productivity as a result of development, with the main objective being price stabilization (by stabilizing inflation) and preventing the spread of poverty by paying attention to the stability of prices of goods and services on the market. The aim of this research is to determine whether there is an influence of Inflation (X1) and CPI (X2) on GRDP (Y) in Bandar Lampung 2012-2019, either partially or simultaneously. In this research the author uses secondary data with a quantitative approach. The data in this research was obtained through the Central Statistics Agency which was accessed online. So in this research the author used a document study method for collecting secondary data. In analyzing this research the author used the classical assumption test method and multiple linear regression models using IBM SPSS Statistics 26. The analytical method used in the research was the classical assumption test. The results of this research show that the GRDP in Bandar Lampung in 2012-2019 was only influenced by inflation, not by the CPI.The Coefficient of determination shows that inflation and CPI have a Simultaneous influence on GRDP of 77,7%.